2016
DOI: 10.1007/s12031-016-0730-y
|View full text |Cite
|
Sign up to set email alerts
|

Aripiprazole Increases the PKA Signalling and Expression of the GABAA Receptor and CREB1 in the Nucleus Accumbens of Rats

Abstract: The GABAA receptor is implicated in the pathophysiology of schizophrenia and regulated by PKA signalling. Current antipsychotics bind with D2-like receptors, but not the GABAA receptor. The cAMP-responsive element-binding protein 1 (CREB1) is also associated with PKA signalling and may be related to the positive symptoms of schizophrenia. This study investigated the effects of antipsychotics in modulating D2-mediated PKA signalling and its downstream GABAA receptors and CREB1. Rats were treated orally with ari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 67 publications
4
34
0
Order By: Relevance
“…Our results showed that aripiprazole upregulated the [ 3 H]muscimol binding level in the PFC, NAcC and CPu of juvenile rats. The results were consistent with the previous papers from our group that both short-term and chronic treatment of aripiprazole increased the expression of GABA A receptor (β-1 subunit) in the NAc of male adult and adolescent rats (Pan et al, 2016a;Pan et al, 2016b). Previously, it has been reported that 1…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results showed that aripiprazole upregulated the [ 3 H]muscimol binding level in the PFC, NAcC and CPu of juvenile rats. The results were consistent with the previous papers from our group that both short-term and chronic treatment of aripiprazole increased the expression of GABA A receptor (β-1 subunit) in the NAc of male adult and adolescent rats (Pan et al, 2016a;Pan et al, 2016b). Previously, it has been reported that 1…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, aripiprazole-induced alteration of NMDA receptor expression may be regulated via acting on dopaminergic D2, such as through D2 receptor downstream protein kinase B (Akt)-glycogen synthase kinase 3 beta (GSK3β) and protein kinase A (PKA) signalling pathways (Beaulieu and Gainetdinov, 2011;Pan et al, 2016a). It has also been reported that the GABA A receptor could be regulated by aripiprazole via D2 receptor downstream PKA signalling (Connelly et al, 2013;Pan et al, 2016b). On the other hand, risperidone is a potent D2 antagonist and also 5-HT2A/C antagonist (Correll, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, ethanol modulation of extrasynaptic GABA A α4 and δ subunits is PKAdependent, and PKA directly affects the expression and function of these receptors, which increase the tonic current in cortical neurons after exposure to a PKA activator, but PKC activation exerts no influence in the tonic current [37]. Aripiprazole increases the expression of GABA A (containing β-1 subunit) receptor in the nucleus accumbens of rats, which is significantly correlated with the enhanced PKA signaling [38]. In addition to hyperalgesia in behavioral tests, we found that the expression (based on western blotting) of GABA A α4, β1, and δ subunits significantly increased in the PAG of Group S + I and Group G1 + I, and the neurons of the PAG also appeared simultaneously immunopositive for GPR30 and GABA A α4, β1, and δ subunits.…”
Section: Discussionmentioning
confidence: 99%
“…Many have similar 3D structures so that it is not easy to rationalize their differing relative potency in different clinical settings. However, significantly SAR for different degrees of internal mobility suggests that molecular dynamics should be an additional factor considered when trying to understand the mode of action of this clinically important family of molecules [36].…”
Section: Approved Antipsychotics In 2015mentioning
confidence: 99%